2023
DOI: 10.1083/jcb.202202102
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin isotype regulation maintains asymmetric requirement for α-tubulin over β-tubulin

Abstract: How cells regulate α- and β-tubulin to meet the demand for αβ-heterodimers and avoid consequences of monomer imbalance is not understood. We investigate the role of gene copy number and how shifting expression of α- or β-tubulin genes impacts tubulin proteostasis and microtubule function in Saccharomyces cerevisiae. We find that α-tubulin gene copy number is important for maintaining excess α-tubulin protein compared to β-tubulin protein. Excess α-tubulin prevents accumulation of super-stoichiometric β-tubulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…β-tubulin overexpression leads to the formation of insoluble aggregates, in contrast, such aggregates do not form when α-tubulin is overexpressed 48 . In both settings, MT functions are highly disrupted 48 . The TBC-DEG binding site to β-tubulin likely evolved to prevent the formation of insoluble polymers of β-tubulin.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…β-tubulin overexpression leads to the formation of insoluble aggregates, in contrast, such aggregates do not form when α-tubulin is overexpressed 48 . In both settings, MT functions are highly disrupted 48 . The TBC-DEG binding site to β-tubulin likely evolved to prevent the formation of insoluble polymers of β-tubulin.…”
Section: Discussionmentioning
confidence: 93%
“…Eukaryotic cells maintain stoichiometric α- and β-tubulin expression, which is critical for MT function and homeostasis 47 . The over-expression of α-tubulin is less toxic than the overexpression of β-tubulin for eukaryotic cells 48 . β-tubulin overexpression leads to the formation of insoluble aggregates, in contrast, such aggregates do not form when α-tubulin is overexpressed 48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To do this we used purified yeast tubulin to build standard curves of αtubulin. Band intensities of cell lysates from log-phase cells grown in rich media were compared to the standard curve and converted from nanograms of protein to molecules per cell (see Material and Methods; Wethekam & Moore, 2023). In cells where we removed the TUB1 intron, the level of α-tubulin across experiments and biological replicates was more consistent and tended to be less than what we observed in wild-type controls (Figure 1B-D).…”
Section: Tub1 Intron Promotes α-Tubulin Expressionmentioning
confidence: 86%
“…Our previous work showed that cells must maintain excess α-tubulin for efficient mitotic timing and to prevent the accumulation of monomeric β-tubulin (Wethekam & Moore, 2023). Conserved features within coding sequences of α-tubulin genes may provide a point of regulation.…”
Section: Introductionmentioning
confidence: 99%